Role of VIA and PAP Smear in the Diagnosis of Cervical Precancers: A Study of 115 C ases - Jahan, RA; Rahman, F; Badruddoza, SM; Nasir, TA; Ahmed, ANNU; Kamal, M (TAJ: Journal of Teachers Association, 2009)
Carcinoma of cervix is the most frequent neoplasm of female genital tract. In Bangladesh cervical cancer is the commonest malignancy of women. This high incidence of cervical cancer is attributed to the lack of screening program, particularly in the women of low socio-economic status. Invasive cervical cancer is preceded by a tong premalignant phase known as cervical intraepithelial neoplasia (CIN). The goal of cervical cancer screening is the detection and treatment of precancer before cancer develops. The aim of this study was to evaluate the test parameters using visual inspection with acetic acid (VIA) and cervical cytology in screening and early diagnosis of the precancerous lesions of cervix. This study deals with 115 cases from Gynecology Outpatient Department of Rajshahi Medical College, Rajshahi from July 2006 to June 2008. After vaginal examination Pap smear was collected, followed by VIA and punch biopsy of cervix. All the data were evaluated by standard statistical methods. The sensitivity of VIA was 94.11% while Pap smear was 64.7%. The specificity of Pap smear was 93.94% while VIA was 57.57%. These two tests may be considered as a suitable early detection technique in the developing countries where other test like HPV-DNA detection is a costly one TAJ 2009; 22(1): 183-189